Pembatasan Hak Veto dalam DK-PBB Terkait Konflik Bersenjata di Suriah - Adi, Danang Wahyu Setyo (CV Rewang Rencang, 2020)
The United Nations (UN) is a new international order organization that was formed after the failure of the League of Nations (LON) after the world war. Within the United Nations, there are important organs, one of which is the Security Council with five permanent members including the United States, Britain, Russia, France, and China. The five permanent members have the authority to issue Veto rights over the policies to be determined. Including one of them is the policy to issue a resolution to cases of armed conflict in Syria. This paper will discuss in more depth the resolution policy in terms of sources of international law and related theories. Including, in this case, the author criticizes the conception of Veto rights attached to the five permanent member states of the UN Security Council which should be aimed at and used to achieve world peace and not for specific interests.